Los tribunales constitucionales y el control del Derecho interno conectado con el comunitario - Alonso García, Ricardo (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2005)
Analysis of the role of national Courts within the European Union, including Constitutional (or Supreme) Courts, before domestic Law implementing Community Law. An effort to avoid, as far as possible, declaring the unconstitutionality of domestic Law, which could entail unnecessary or incoherent declarations of unconstitutionality of Community Law.